Evaluation of Antibody-Dependent Fc-Mediated Viral Entry, as Compared With Neutralization, in SARS-CoV-2 Infection - Wieczorek, Lindsay; Zemil, Michelle; Merbah, Mélanie; Dussupt, Vincent; Kavusak, Erin; Molnar, Sebastian; Heller, Jonah; Beckman, Bradley; Wollen-Roberts, Suzanne; Peachman, Kristina K.; Darden, Janice M.; Krebs, Shelly; et al. (Frontiers in Immunology, 2022)
Fc-mediated virus entry has been observed for many viruses, but the characterization of this activity in convalescent plasma against SARS-CoV-2 Variants of Concern (VOC) is undefined. In this study, we evaluated Fc-mediated viral entry (FVE) on FcRIIa-expressing HEK293 cells in the presence of SARS-CoV-2 convalescent plasma and compared it with SARS-CoV-2 pseudovirus neutralization using ACE2-expressing HEK293 cells. The plasma were collected early in the pandemic from 39 individuals. We observed both neutralization and FVE against the infecting Washington SARS-CoV-2 strain for 31% of plasmas, neutralization, but not FVE for 61% of plasmas, and no neutralization or FVE for 8% of plasmas. Neutralization titer correlated significantly with the plasma dilution at which maximum FVE was observed, indicating Fc-mediated uptake peaked as neutralization potency waned. While total Spike-specific plasma IgG levels were similar between plasma that mediated FVE and those that did not, Spike-specific plasma IgM levels were significantly higher in plasma that did not mediate FVE. Plasma neutralization titers against the Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1) and Delta (B.1.617.2) VOC were significantly lower than titers against the Washington strain, while plasma FVE activity against the VOC was either higher or similar. This is the first report to demonstrate a functional shift in convalescent plasma antibodies from neutralizing and FVE-mediating against the earlier Washington strain, to an activity mediating only FVE and no neutralization activity against the emerging VOC, specifically the Beta (B.1.351) and Gamma (P.1) VOC. It will be important to determine the in vivo relevance of these findings.